Legal Analysis of Punishment for Perpetrators of Violence Against Children in the Perspective of Substantive Justice (Study of Decision Number 103/Pid.Sus/2017/PN Psb) - Setyawan, Iwan; Pardede, Desi Yeni; Chandra, Stacie Stravinsky (Universitas Medan Area, 2025)
This study aims to analyze the application of the law to perpetrators of child abuse in Decision Number 103/Pid.Sus/2017/PN Psb and to assess the extent to which the decision reflects the principles of justice and legal protection for child victims. The phenomenon of violence against children in Indonesia continues to increase, but the response of criminal justice often does not fully support the best interests of children. A qualitative approach with a case study design was used in this study, focusing on one court decision as the unit of analysis. Data were collected through court decision documentation, literature studies, and reviews of laws and regulations, which were analyzed descriptively-qualitatively to reveal the suitability of the application of the law to the principles of child protection. The results of the study indicate that normatively, the judge has applied the provisions in Article 80 paragraph (1) in conjunction with Article 76C of Law No. 35 of 2014 by imposing a sentence on the defendant. However, the decision does not fully reflect substantive justice because it does not contain an order for psychological recovery for child victims. This finding indicates that the legal approach still tends to be repressive and has not touched on holistic aspects of recovery. This study contributes to the understanding of the weaknesses of the juvenile criminal justice system in ensuring comprehensive justice. Further research is recommended to examine the implementation of the decision and its impact on the psychosocial conditions of child victims of violence.